Exploring individual and organizational mechanisms of implementation of evidence-based practices for the inclusion of elementary students with autism: Study protocol. (2021) - Locke, Jill; Hugh, Maria L.; Pullmann, Michael D.; Cook, Heather; Coifman, Jessica; McRee, Erin; Joshi, Mahima; Lyon, Aaron R.; Schwartz, Ilene
Highlights: This study uses mixed methods to explore educators' use of evidence-based practices (EBP). This study will identify practices to support inclusion of children with autism in public schools. This study will identify malleable implementation targets to increase EBP use in schools. Abstract: The increased prevalence of autism in the United States (1 in 54 youth) requires educators to implement evidence-based practices (EBPs). However, it is unclear which EBPs, if any, general and special education teachers and paraeducators are commonly trained to use or whether they consistently use those EBPs to support the inclusion of students with autism. The purpose of this protocol is to understand EBP use in inclusive settings and examine the malleable individual and organizational factors that promote teachers' and paraeducators' use of EBPs to meaningfully include and retain children with autism in general education settings and how this use relates to children's outcomes. These data will support the identification of targeted implementation strategies for successful EBP use.